PERAN GURU DALAM PENGUATAN KARAKTERDISIPLIN SISWA DI KELAS IV MI NW KARANG BATA MATARAM TAHUN PELAJARAN 2025/2026 - Walidaini, Shielda Rizky; Imtihan, Nurul; Asriadi, Lalu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the importance of strengthening disciplinary character among elementary school students, particularly in Madrasah Ibtidaiyah, as there are still students who show undisciplined behavior such as coming late, being less orderly during lessons, and not obeying school rules. This study aimed to describe the role of teachers in strengthening the disciplinary character of fourth-grade students at MI NW Karang Bata Mataram and to identify the obstacles faced in its implementation. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of fourth-grade teachers, the principal, and students. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results showed that teachers play an important role in strengthening students’ disciplinary character through role modeling, habituation, motivation, implementation of classroom rules, supervision, and the provision of educational rewards and sanctions. Teachers also act as facilitators and motivators in creating a learning environment that supports the development of disciplined behavior among students. Strengthening disciplinary character had a positive impact on students’ behavior, such as improving punctuality, obedience to school regulations, responsibility in completing assignments, and orderly attitudes during the learning process. However, its implementation still faced challenges, including differences in students’ characters, lack of family support, and limited supervision outside school.